1997
DOI: 10.1002/eji.1830270822
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor blockade in actively induced experimental autoimmune encephalomyelitis prevents clinical disease despite activated T cell infiltration to the central nervous system

Abstract: Recently, we demonstrated that experimental autoimmune encephalomyelitis (EAE) in the rat, passively transferred using myelin basic protein (MBP)-reactive encephalitogenic CD4+ T cells, was preventable by administration of a p55-tumor necrosis factor-IgG fusion protein (TNFR-IgG). This was despite quantitatively and qualitatively normal movement of these MBP-specific T cells to the central nervous system (CNS). To extend these findings, the effect of TNFR-IgG on EAE actively induced by injection of MBP in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 47 publications
(27 reference statements)
6
67
0
1
Order By: Relevance
“…Although some dTNFR-tsF-treated mice in this study did develop EAE, there were a number of animals that were completely protected from EAE, showing stable weight progression and no CNS infiltrate. This may indicate a higher degree of TNF neutralization by the dTNFR-tsF cells, inhibiting TNF-induced cachexia, compared with the bolus protein administration in some studies (23). This study also demonstrates that both the development of acute phase EAE and the development of relapse may also be inhibited by dTNFR.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Although some dTNFR-tsF-treated mice in this study did develop EAE, there were a number of animals that were completely protected from EAE, showing stable weight progression and no CNS infiltrate. This may indicate a higher degree of TNF neutralization by the dTNFR-tsF cells, inhibiting TNF-induced cachexia, compared with the bolus protein administration in some studies (23). This study also demonstrates that both the development of acute phase EAE and the development of relapse may also be inhibited by dTNFR.…”
Section: Discussionmentioning
confidence: 66%
“…‫,ء‬ p Ͻ 0.05; ‫,ءء‬ p Ͻ 0.005; ‫,ءءء‬ p Ͻ 0.0002 compared with tsF-treated mice. loss correlates with blood-brain barrier dysfunction and cellular recruitment (24); and in some cases of TNF-specific protein therapy, animals showed weight loss even though disease was reduced (23). Although some dTNFR-tsF-treated mice in this study did develop EAE, there were a number of animals that were completely protected from EAE, showing stable weight progression and no CNS infiltrate.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…TNF-α also has suspected immunoregulatory activities [16,17]. Reports on TNF-α−/− mice with EAE have shown conflicting results: whereas Liu et al [18] reported more severe EAE in TNF-α−/− C57BL/ 6 mice immunized with MOG, Körner et al [19] observed a delayed first attack of EAE using the same mice and antigen. In the present study, we focused on cytokine production to elucidate the mechanisms of relapse in CREAE mice immunized with MOG 35-55 and witnessed that IFN-γ and TNF-α production by spleen cells and mRNA expression in the CNS were elevated only during the first attack.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ is produced by activated T cells (mostly Th1) and macrophages, and its elevated expression at the site of inflammation occurs during the critical phase of disease, 11 at the time when the 'secondary influx' of leukocytes is apparent. 3 Except for a single recent study carried out in genetically modified animals, 36 all investigators agree that TNF-␣ contributes to the pro-inflammatory process in EAE, and probably MS. 25,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Thus, inhibition of TNF-␣ activity by either neutralizing antibodies or soluble TNF receptor therapy, effectively prevents, or even reverses EAE. 25,42,45,[47][48][49][50][51] Overexpression of TNF-␣ in the CNS aggravated the dis-ease, 46 whereas genetically impaired expression of this gene inhibited the development and progression of disease.…”
Section: Introductionmentioning
confidence: 99%